Towards Digital Intervention: Overview Of Dyscalculia In Indonesia - cahyana, cahyana; Azimi, Indra (Jurnal Sistem Komputer, 2015)
Dyscalculia is a learning disability. It affects the arithmetic ability of student, and usually can’t be separated from mathematical learning difficulty. It is usually occurred in early stage of learning, and unless an intervention (traditional or digital) is given, the disability will persist until adulthood. This paper will present an overview of current condition of dyscalculia in Indonesia. Researches in traditional and digital intervention and the role of computer-assisted instruction are also discussed.